Genital herpes and pregnancy - Tilli, Miguel (Brazilian Journal of Sexually Transmitted Diseases, 2023)
The genital infection due to herpes simplex virus (HSV) during pregnancy is uncommon, but in some cases may be dangerous to the newborn.The maternal-fetal transmission may occur during the primary infection at the onset of labor or due to reactivated latent maternal infection. The pre-sent revision focus on epidemiological, clinic, diagnosis and therapeutics aspects of HSV infection in pregnant women. Another aim is to offer pre-vention measures in order to reduce the risk of the perinatal transmission of the virus.